Haematochezia from a Splenic Artery Pseudoaneurysm Communicating with Transverse Colon: A Case Report and Literature Review - James O’Brien; Francesca Muscara; Aser Farghal; Irshad Shaikh (Case Reports in Vascular Medicine)
Splenic artery aneurysms (SAA) are the third most common intra-abdominal aneurysm. Complications include invasion into surrounding structures often in association with preexisting pancreatic disease. We describe an 88-year-old female, with no history of pancreatic disease, referred with lower gastrointestinal bleeding. CT angiography showed a splenic artery pseudoaneurysm with associated collection and fistula to the transverse colon at the level of the splenic flexure. The pseudoaneurysm was embolised endovascularly with metallic microcoils. Rectal bleeding ceased. The patient recovered well and follow-up angiography revealed no persistence of the splenic artery pseudoaneurysm. SAA rupture results in 29%–50% mortality. Experienced centres report success with the endovascular approach in haemodynamically unstable patients, as a bridge to surgery, and even on a background of pancreatic disease. This case highlights the importance of prompt CT angiography, if endoscopy fails to identify a cause of gastrointestinal bleeding. Endovascular embolisation provides a safe and effective alternative to surgery, where anatomical considerations and local expertise permit.